The implementation of Malay language education policy and the linguistic landscape in Malaysia - Soon, Chiow Thai; Loi, Chek Kim (2019)
This ethnographic research uses the applied linguistic landscape of Ben-Rafael (2009) to examine the choices of language practice (Spolsky, 2009) reflected through 459 Romanised names of the company on an island in Malaysia named Labuan. One of the outcomes of this study shows Malaysians are basically bilingual and about half of the names of the company are bilingual. However, the use of Malay language in naming the companies on the island is low though the Malay language is the national language of the country and the Malaysian government has implemented the Malay language education policy since independence in 1957. There are only 13% of company names presented in pure Malay language comparing to those in pure English (45%) and in code-mixing of Malay language and English or other languages (42%). Besides a low percentage of using the Malay language in the company names, incorrect uses of the language were identified. The study suggests the Malaysian government specifically the local government considers the company name written in both Malay language and English instead of merely in the Malay language when it comes to approving the application of new company licenses.